Experimental investigation of the hydroelastic and the structural response of a moored pontoon-type modular floating breakwater with flexible connectors - Loukogeorgaki, Eva; Yağcı, Oral; Loukogeorgaki, Eva; Lentsiou, Elpida Niki; Asel, Murat (Elsevier Science Bv, Po Box 211, 1000 AE Amsterdam, Netherlands, 2017)
In this paper, 3D experiments are conducted aiming at the combined investigation of the hydroelastic and the structural (connectors' internal forces) response of a pontoon-type modular Floating Breakwater (FB), consisting of flexibly connected, moored with chains modules, under the action of perpendicular and oblique regular waves. Regarding the FB's hydroelastic response (i.e. 3D displacements of the modules under the wave action), video recording of the horizontal and the vertical displacements of specific points on the FB relatively to some fixed points is implemented, and this response is determined through an appropriate image processing procedure. For asseasing the FB's structural response, strain rosettes are utilized, enabling the evaluation of the connectors' forces through the corresponding strains' measurements. The effect of the incident wave characteristics (period, height, obliquity) on the FB's hydroelastic and structural response is analyzed. The correlation between the connectors' forces and the FB's hydroelastic response is extensively discussed. The FB's hydroelastic and structural response depends strongly upon the wave period, while the wave height and obliquity affect this response in the low frequency range. Strong dependency of the connectors' forces upon the existence or not of a FB's intense deformed shape is demonstrated.
Keywords: Floating breakwater; Flexible connectors; Hydroelastic response; Connectors' internal forces; 3D experiments; Wire Rope; Body